Engineering of Fc Fragments with Optimized Physicochemical Properties Implying Improvement of Clinical Potentials for Fc-Based Therapeutics - Yang, Chunpeng; Gao, Xinyu; Gong, Rui (Frontiers in Immunology, 2018)
Therapeutic monoclonal antibodies (mAbs) and Fc-fusion proteins are successfully used in treatment of various diseases mainly including cancer, immune disease and viral infection, which belong to the Fc-based therapeutics. In recent years, Fc-derived antibody domains are also shown to be potential to Fc-based therapeutics. To increase the druggability of Fc-based therapeutic candidates, many efforts have been made in optimizing physicochemical properties and functions mediated by Fc fragment. The desired result is that we can simultaneously obtain Fc variants with increased physicochemical properties in vitro and capacity of mediating appropriate functions in vivo. However, changes of physicochemical properties of Fc may result in alternation of Fc-mediated functions and vice versa, which leads to undesired outcomes for further development of Fc-based therapeutics. Therefore, whether modified Fc fragments are suitable for achievement of expected clinical results or not needs to be seriously considered. Now, this question comes to be noticed and should be figured out to make better translation from the results of laboratory into clinical applications. In this review, we summarize different strategies on engineering physicochemical properties of Fc, and preliminarily elucidate the relationships between modified Fc in vitro and the subsequent therapeutic influence in vivo.